Pengaruh Consumer Animosity dan Negative E-Wom Terhadap Purchase Intention: Peran Mediasi Brand Image Pada KFC Indonesia - Angwen Constantine; Barkah Barkah; Ahmadi Ahmadi; Heriyadi Heriyadi; Wenny Pebrianti (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The global fast-food industry continues to experience significant growth, with Indonesia emerging as a strategic market. However, KFC faces serious challenges due to boycott calls related to global geopolitical issues. This study aims to analyze the effects of consumer animosity and negative electronic word of mouth (negative e-WOM) on purchase intention, with brand image as a mediating variable in the context of KFC Indonesia. A quantitative approach was employed using an online survey of 200 Indonesian respondents who were aware of the boycott issue involving KFC. Data were analyzed using SmartPLS version 4.0 with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results indicate that consumer animosity and negative e-WOM have significant negative effects on brand image. Negative e-WOM significantly influences purchase intention, while consumer animosity does not have a significant direct effect. Nevertheless, brand image plays a significant mediating role in the relationships among the variables. These findings highlight the critical role of brand image in shaping consumer perceptions and behavioral intentions. Strategically, KFC Indonesia needs to strengthen brand image, enhance reputation recovery efforts, and manage public perceptions more effectively to reduce the negative impact of adverse information and consumer sentiment.